# -x=2.8(3x+5)-2.6x

## Simple and best practice solution for -x=2.8(3x+5)-2.6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -x=2.8(3x+5)-2.6x equation:

-x=2.8(3x+5)-2.6x
We move all terms to the left:
-x-(2.8(3x+5)-2.6x)=0
We add all the numbers together, and all the variables
-1x-(2.8(3x+5)-2.6x)=0

We calculate terms in parentheses: -(2.8(3x+5)-2.6x), so:
2.8(3x+5)-2.6x
We add all the numbers together, and all the variables
-2.6x+2.8(3x+5)
We multiply parentheses
-2.6x+8.4x+14
We add all the numbers together, and all the variables
5.8x+14
Back to the equation:
-(5.8x+14)

We get rid of parentheses
-1x-5.8x-14=0
We add all the numbers together, and all the variables
-6.8x-14=0
We move all terms containing x to the left, all other terms to the right
-6.8x=14
x=14/-6.8
x=-2+0.4/6.8

`